1977
DOI: 10.1111/j.1476-5381.1977.tb08405.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intravenous Anaesthetics on the Cardiovascular System of the Rabbit

Abstract: 1 A pithed rabbit preparation is described that allows selective stimulation of the vertebral outflows. 2 The responses to stimulation of sympathetic vasopressor fibres were blocked by hexamethonium and phentolamine but potentiated by cocaine, whereas the responses to stimulation of cardioaccelerator fibres were blocked by propranolol. 3 Ketamine, althesin and pentobarbitone enhanced the effects of noradrenaline and attenuated the effects of sympathetic nerve stimulation. Thiopentone enhanced the effects of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In order to take a static image of the rabbits, we used ketamine as an anesthetic agent in this study. McGrath and MacKenzie showed that ketamine can attenuate the effects of sympathetic nerve stimulation [17]. In this study, all animals showed a similar weight gain and received the same amount of ketamine for anesthesia.…”
Section: Cholesterol and Sympathetic Functionmentioning
confidence: 74%
“…In order to take a static image of the rabbits, we used ketamine as an anesthetic agent in this study. McGrath and MacKenzie showed that ketamine can attenuate the effects of sympathetic nerve stimulation [17]. In this study, all animals showed a similar weight gain and received the same amount of ketamine for anesthesia.…”
Section: Cholesterol and Sympathetic Functionmentioning
confidence: 74%
“…Further variation in results (and subsequent conclusions) arises from the differing effects of different anaesthetics in the peripheral vasculature (Clark & MacCannell, 1975;Miller & Wiegman, 1977), on cardiac function (Jandhyala & Buckley, 1977;McGrath & MacKenzie, 1977), on circulating catecholamines (Pettinger et al, 1975) or centrally (Bielicki & Kreiglstein, 1977;Sung, Frederickson & Holtzman, 1973).…”
Section: Anaesthesia and Central Cardiovascular Controlmentioning
confidence: 99%
“…Male New Zealand white rabbits (3-4 kg) were initially anaesthetized with Althesin injected via an ear vein and were pithed under halothane anaesthesia (McGrath & McKenzie, 1977), then artificially ventilated with 100% oxygen. Right and left carotid arteries were cannulated to monitor arterial blood pressure and for the addition of propranolol at 30 min intervals, respectively.…”
Section: Methodsmentioning
confidence: 99%